Mother-Daughter Relations in the Novel “The Joy Luck Club” by Amy Tan (Eurasian Journal of Humanities and Social Sciences, 2022)
There are many of Chinese American authors who did great contribution to the literature but among them Chinese American writer Amy Tan plays an important role. Her works mostly explore mother-daughter relationships. Moreover, the connection of the past and the present is typical of Tan's style. “The Joy Luck Club” is one of her the most famous novels which focuses on the relationship between an immigrant Chinese mother and her American-born daughter